2004
DOI: 10.1097/01.mlr.0000108747.51198.41
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Occasional and Frequent Emergency Department Users

Abstract: The uninsured do not use more ED visits than the insured population as is sometimes argued. Instead, the publicly insured are overrepresented among ED users. Frequent ED users do not appear to use the ED as a substitute for their primary care but, in fact, are a less healthy population who need and use more care overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
154
4
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(184 citation statements)
references
References 20 publications
24
154
4
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Despite varying definitions, high-frequency ED users have been described together as typically poor, male, members of minority groups, chronically ill, socially isolated, and frequently presenting with psychiatric or substance abuse problems. 2,5,10,11 The literature suggests, however, that characteristics differ between frequent users with less than 20 visits per year and those with more than 20 visits. 12,13 Frequent ED use places an economic burden on the health care system and may also indicate that basic needs have gone unmet.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Despite varying definitions, high-frequency ED users have been described together as typically poor, male, members of minority groups, chronically ill, socially isolated, and frequently presenting with psychiatric or substance abuse problems. 2,5,10,11 The literature suggests, however, that characteristics differ between frequent users with less than 20 visits per year and those with more than 20 visits. 12,13 Frequent ED use places an economic burden on the health care system and may also indicate that basic needs have gone unmet.…”
mentioning
confidence: 99%
“…Contrary to popular belief, these patients generally do not lack health insurance or a primary care physician. [20][21][22][23][24] Several studies have even found that a change in health insurance status is related to increased ED use. 20,25 With universal access to health care in Ontario, ED use should theoretically be equal throughout the population.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is conflicting evidence about whether it is primary care service characteristics or patient characteristics that determine emergency department use. In North America, some studies have found that emergency department users are more likely to be nonwhite, poor, and less educated, [7][8][9] although other studies have shown that a focus on systems issues may impact on emergency department use. 10,11 Second, much of the research that links primary care supply factors to hospital attendances is based in the North American context and not necessarily applicable to the NHS.…”
Section: Introductionmentioning
confidence: 99%